2015
DOI: 10.1162/tacl_a_00141
|View full text |Cite
|
Sign up to set email alerts
|

Design Challenges for Entity Linking

Abstract: Recent research on entity linking (EL) has introduced a plethora of promising techniques, ranging from deep neural networks to joint inference. But despite numerous papers there is surprisingly little understanding of the state of the art in EL. We attack this confusion by analyzing differences between several versions of the EL problem and presenting a simple yet effective, modular, unsupervised system, called Vinculum, for entity linking. We conduct an extensive evaluation on nine data sets, comparing Vincul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
160
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(172 citation statements)
references
References 14 publications
(24 reference statements)
2
160
0
1
Order By: Relevance
“…We also assume that the KB is accompanied by an entity candidate selector that takes as input some text and returns a list of C potential entity links, each consisting of the start and end indices of the potential mention span and M m candidate entities in the KG: In practice, these are often implemented using precomputed dictionaries (e.g., CrossWikis; Spitkovsky and Chang, 2012), KB specific rules (e.g., a WordNet lemmatizer), or other heuristics (e.g., string match; Mihaylov and Frank, 2018). Ling et al (2015) showed that incorporating candidate priors into entity linkers can be a powerful signal, so we optionally allow for the candidate selector to return an associated prior probability for each entity candidate. In some cases, it is beneficial to over-generate potential candidates and add a special NULL entity to each candidate list, thereby allowing the linker to discriminate between actual links and false positive candidates.…”
Section: Knowledge Basesmentioning
confidence: 99%
“…We also assume that the KB is accompanied by an entity candidate selector that takes as input some text and returns a list of C potential entity links, each consisting of the start and end indices of the potential mention span and M m candidate entities in the KG: In practice, these are often implemented using precomputed dictionaries (e.g., CrossWikis; Spitkovsky and Chang, 2012), KB specific rules (e.g., a WordNet lemmatizer), or other heuristics (e.g., string match; Mihaylov and Frank, 2018). Ling et al (2015) showed that incorporating candidate priors into entity linkers can be a powerful signal, so we optionally allow for the candidate selector to return an associated prior probability for each entity candidate. In some cases, it is beneficial to over-generate potential candidates and add a special NULL entity to each candidate list, thereby allowing the linker to discriminate between actual links and false positive candidates.…”
Section: Knowledge Basesmentioning
confidence: 99%
“…Incorporating the fine-grained types of a mention m can help rank entities of the appropriate type higher than others (Ling et al, 2015;Gupta et al, 2017;Raiman and Raiman, 2018). For instance, knowing the correct type of mention [Liverpool] as sports_team and constraining linking to entities with the relevant type, encourages disambiguation to the correct entity.…”
Section: Including Type Informationmentioning
confidence: 99%
“…EL [5] is similar to WSD [28,29], but it is about linking "potentially partial" entity mentions to a target KB, that has an encyclopaedic nature [30,29]. The EL problem is presented in several variants and focussing on different types of data [31,32,33,34,35,36], and it has been the subject of task-oriented evaluation procedures and benchmarks [37,38]. A few EL systems work in an unsupervised way [39,33], but the KB is still given.…”
Section: Related Workmentioning
confidence: 99%
“…Named Entity Recognition (NER) focusses on discovering mentions to entities, and it is also a basic module of several EL systems [40]. However NER is about proper nouns, as frequently is EL [31], while here we also consider common nouns. Moreover, NER systems output the entity type (person, location, etc.)…”
Section: Related Workmentioning
confidence: 99%